Analisis Korosifitas Baja Ringan dengan Metoda Laser Induced Breakdown Spectroscopy (LIBS) - Siti Raudatul Jannah; Ni Nyoman Ratini; Windarjoto Windarjoto; Hery Suyanto (Kappa Journal, 2021)
Method has been carried out. Research is done on mild steel zincalume type with immersion treatment (NaCl 3.5%) for 10 days, and 30 days and without immersion. Mild steel is laser irradiated (Nd-YAG 1064 nm, 7 ns) with energy of 120 mJ, and the data is taken with an accumulation of 3, delay time of 0.5 µs. Elements identification is done by taking data from up to 75 Î¼m from the surface. The results of the analysis with LIBS showed immersion for 10 days, the corrosion rate and hardness of mild steel increased with 30 days immersion. The increase in the corrosion rate of mild steel is indicated by decreasing the value of dissolved oxygen intensity, the electrochemical reaction is fast. The decrease in the corrosion rate is indicated by the increase in the intensity value of Zn and Al elements associated with the formation of a passive film on the metal surface as a protective layer to protect further corrosion attacks.DOI : 10.29408/kpj.v5i1.3446